3D Modeling of Subsurface Lawanopo Fault In Southeast Sulawesi, Indonesia Using Grablox and its Consequence to Geohazard - Triani Triani; Rofiqul Umam; Sismanto Sismanto (Faculty of Geography, Universitas Gadjah Mada, 2021)
Lawanopo Fault is a horizontal shear fault (sinistral strike-slip) found in Southeast Sulawesi province and is thought to be active during Plio-Pleistocene or mid-late Miocene to the present. This study has been carried out which aims to find out the geometric shapes below the surface of the Lawanopo fault using complete Bouguer anomaly (ABL) data. The ABL data is projected onto a flat plane using the Dampney method at an altitude of 8 km, and the separation of local and regional anomalies is carried out using the upward continuation method at an altitude of 60 km. Three-dimensional (3D) modeling under the surface of the Lawanopo fault is done using the computer program Grablox. Data processing techniques using Singular Value Decomposition (SVD) and Occam inversion. The results showed that a high gravity anomaly of 190-225 mGal was caused by an igneous rock below the surface with a density of 2.7-3.33 gr/cm3 and a thickness of about 13 km, a moderate anomaly of 175-187 mGal caused by Paleozoic igneous rocks aged Carbon with a density of 2.6-2.9 gr/cm3 and a thickness of about 25 km. Low anomaly 115-160 mGal is caused by rocks with a density of 2.0-2.5 gr/cm3 and a thickness of about 22-23 km. The Lawanopo fault constituent rocks consist of alkaline rocks in the basement covered by sediment and metamorphic with a depth of Lawanopo fault more than 15 km and begin to be seen at a depth of 4.3 km of the surface. it is known that the area around the Lawanopo fault is an area prone to earthquakes. But, based on the soil and rock structure around the Lawanopo fault, the compactness and attenuation levels in reducing earthquake waves are quite good, so that land use around the Lawanopo fault tends to be safe.